After 9 Years of 3-Column Osteotomies, Are We Doing Better? Performance Curve Analysis of 573 Surgeries With 2-Year Follow-up. Issue 1 (21st July 2017) - Diebo, Bassel G; Lafage, Virginie; Varghese, Jeffrey J; Gupta, Munish; Kim, Han Jo; Ames, Christopher; Kebaish, Khaled; Shaffrey, Christopher; Hostin, Richard; Obeid, Ibrahim; Burton, Doug; Hart, Robert A; et al.
Abstract: BACKGROUND: In spinal deformity treatment, the increased utilization of 3-column (3CO) osteotomies reflects greater comfort and better training among surgeons. This study aims to evaluate the longitudinal performance and adverse events (complications or revisions) for a multicenter group following a decade of 3CO. OBJECTIVE: To investigate if performance of 3CO surgeries improves with years of practice. METHODS: Patients who underwent 3CO for spinal deformity with intra/postoperative and revision data collected up to 2 yr were included. Patients were chronologically divided into 4 even groups. Demographics, baseline deformity/correction, and surgical metrics were compared using Student t -test. Postoperative and revision rates were compared using Chi-square analysis. RESULTS: Five hundred seventy-three patients were stratified into: G1 (n = 143, 2004-2008), G2 (n = 142, 2008-2009), G3 (n = 144, 2009-2010), G4 (n = 144 2010-2013). The most recent patients were more disabled by Oswestry disability index (G4 = 49.2 vs G1 = 38.3, P = .001), and received a larger osteotomy resection (G4 = 26° vs G1 = 20°, P = .011) than the earliest group. There was a decrease in revision rate (45%, 35%, 33%, 30%, P = .039), notably in revisions for pseudarthrosis (16.7% G1 vs 6.9% G4, P = .007). Major complication rates also decreased (57%, 50%, 46%, 39%, P = .023) as did excessive blood loss (>4 L, 27.2 vs 16.7%, P = .023) and bladder/bowel deficit (4.2% vs 0.7% P = .002). Successful outcomes (no complications or revision) significantly increased ( P = .001). CONCLUSION: Over 9 yr, 3COs are being performed on an increasingly disabled population while gaining a greater correction at the osteotomy site. Revisions and complication rate decreased while success rate improved during the 2-yr follow-up period.